FOREIGN LANGUAGE TRAINING IN TRANSLATION AND INTERPRETING DEGREES IN SPAIN: A STUDY OF TEXTUAL FACTORS - Laura Cruz García (Universidad Peruana de Ciencias Aplicadas, 2017)
Foreign language teaching and learning has received a considerable amount of scholarly attention across different stages of education, particularly in the case of English. Apart from language training in general contexts, language for special purposes also constitutes a prolific field of study. However, less research has been conducted on the foreign-language training needs of trainee translators and interpreters and the corresponding teaching methodologies. In order to gain insight into actual teaching practices in this area in Spanish universities, we have studied the methodological approaches used in the classroom by 58 foreign language lecturers at 13 Translation and Interpreting Faculties in Spain, through a research project of Universidad de Las Palmas de Gran Canaria (Spain). Information was compiled from the responses to an ad hoc questionnaire created for this purpose, sent out by email and filled out on a voluntary basis. This article describes the uses made of texts in foreign language classes, to which end we will focus on the responses to one of the questions posed in the questionnaire. One of the key findings of the study is the preponderance of lexical, semantic, morphological and syntactic features, potentially implying teaching methodologies akin to those used in other education settings.